2011
DOI: 10.1002/14651858.cd008471.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field stimulation for treating delayed union or non-union of long bone fractures in adults

Abstract: Sharrard WJ. A double-blind trial of pulsed electromagnetic fields for delayed union of tibial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
0
40
1
2
Order By: Relevance
“…Yet another line evidence derives from the documented observation in humans that fracture healing is improved upon the stimulation of the affected bone with pulsed electromagnetic stimulation [92]. Our groups have recently demonstrated that PEMS enhances myogenesis of C2C12 myoblasts [93].…”
Section: Evidence Of Muscle-bone Crosstalkmentioning
confidence: 99%
“…Yet another line evidence derives from the documented observation in humans that fracture healing is improved upon the stimulation of the affected bone with pulsed electromagnetic stimulation [92]. Our groups have recently demonstrated that PEMS enhances myogenesis of C2C12 myoblasts [93].…”
Section: Evidence Of Muscle-bone Crosstalkmentioning
confidence: 99%
“…An electric field is known to promote bone formation in vitro and in vivo [46][47][48][49]; that is the working theory behind capacitative electric field devices. In 2011, Griffin and colleagues [50] performed a Cochrane database systematic review in which they examined 4 studies involving 125 participants with either delayed union or nonunion of long bones. Those authors concluded that although there might have been some positive effects from treatment with capacitative electric field devices, the current evidence of that benefit is inconclusive and insufficient.…”
Section: Antigravity Treadmillsmentioning
confidence: 99%
“…The process is a complicated procedure, on both a macroscopic and microscopic level [5]. Because of the precise balance required between anabolic and catabolic phases, delayed unions, mal-unions and non-unions are common, occurring in 5-10% of all long bone fractures [6]. Hernigou et al [7] define a delayed union as a fracture site continuing to sustain clinical and radiological signs of fracture outside of the expected healing time or the absence of signs of progressive repair between the third and sixth months of repair following a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Hernigou et al [7] define a delayed union as a fracture site continuing to sustain clinical and radiological signs of fracture outside of the expected healing time or the absence of signs of progressive repair between the third and sixth months of repair following a fracture. Mal-unions are defined as a pathological union of a fracture, usually involving shortening and rotational or angular deformity [1], while non-unions are defined as a lack of union within the expected healing time [6]. Although there is a lack of a standardised definition of these pathologies, they are clinically significant and have an impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%